Assessing the effectiveness of using Kahoot! to improve students’ engagement during grammar lessons / Zawani Badri, Rafidah Amat and Mas Aida Abd Rahim - Badri, Zawani; Amat, Rafidah; Abd Rahim, Mas Aida (Universiti Teknologi MARA, Kedah, 2025)
This study examines the effectiveness of using Kahoot! as a gamification platform to enhance ESL students’ engagement during grammar lessons. Based on the Gamification Acceptance Model (GAM), the study investigates in what way perceived utility, convenience of use, attitude toward gamification, skill engagement, and interaction engagement affect students' learning experiences. Using a mixed-method approach, this study included 41 first-semester diploma-level ESL students. Quantitative information was obtained through an adapted GAM 18-item questionnaire, and qualitative insights came from 2 semi-structured interviews conducted with 12 participants. The findings reveal that integrating Kahoot! into grammar instruction significantly improves students' engagement, attitudes, and performance. This platform will help us in making passive lessons more interactive and entertaining while also fostering an interactive and engaging learning atmosphere. The quantitative analysis indicates that the perceived usefulness and ease of use of the platform is a direct reason for their positive attitude towards gamification. Qualitative analytics helped validate these insights by emphasizing the two major drivers behind engagement: skill-based and interactivity-based components. The present study illustrates the effectiveness of gamification in ESL classes, especially when it comes to teaching some difficult topics, such as grammar. It calls for wider adoption of Kahoot! in language acquisition to maximize interaction and results. In order to enhance the advantages of this strategy in promoting 21 century education, future studies should address its implementation in different educational settings and other language abilities.